Max 2 [videorecording (DVD)] : White House hero - Levant, Brian; Austin, Zane; Capaldi, Francesca; Munro, Lochlyn, 1966- (Warner Bros. Home Entertainment, 2017)
When the Secret Servce dog is temporarily out on maternity leave, Max is assigned to the White House as a temporary replacement.